The psychological implications of COVID-19 over the eighteen-month time span following the virus breakout in Italy - Ropi, Ingrid; Lillo, Margherita; Malavasi, Matteo; Argentieri, Alessandro; Barbieri, Aurora; Lou, Baowen; Barbieri, Diego Maria; Passavanti, Marco (Frontiers in Psychology, 2024)
Background: In a short time, the COVID-19 pandemic has exerted a huge impact on many aspects of people's lives with a number of consequences, an increase in the risks of psychological diseases being one of them.The aim of this experimental study, based on an eighteen-month follow-up survey, is to assess the psychological effects of the COVID-19 pandemic, in particular, changes in stress, anxiety and depression levels, and the risks of developing Post-Traumatic Stress Disorder (PTSD).Methods: A follow-up survey was performed on a sample of 184 Italian individuals to collect relevant information about the psychological impact of COVID-19. Predictors of the components of the psychological impact were calculated based on the ANCOVA model.Results: The analysis of the online questionnaires led to the conclusion that a high percentage of the participants suffer from levels of stress, anxiety and depression higher than normal as well as an increased risk of PTSD. The severity of such disorders significantly depends on gender, the loss of family members or acquaintances due to the pandemic, the amount of time spent searching for COVID-19 related information, the type of information sources and, in part, on the level of education and income. The time factor had a more severe effect on the low-income population.Conclusions: COVID-19 has entailed a very strong psychological impact on the Italian population also depending on the coping strategies adopted, the level of mindful awareness, sociodemographic variables, people's habits and the way individuals use the available means of communication and information.